2018
DOI: 10.1111/acps.12987
|View full text |Cite
|
Sign up to set email alerts
|

Severity, course trajectory, and within‐person variability of individual symptoms in patients with major depressive disorder

Abstract: Background Depression shows a large heterogeneity of symptoms between and within persons over time. However, most outcome studies have assessed depression as a single underlying latent construct, using the sum score on psychometric scales as an indicator for severity. This study assesses longitudinal symptom‐specific trajectories and within‐person variability of major depressive disorder over a 9‐year period. Methods Data were derived from the Netherlands Study of Depression and Anxiety (NESDA). This study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…These studies have indicated that suicidality is one of the most stable depressive symptoms over time (meaning it has low variability), whereas the opposite holds for depressed mood and anhedonia, which vary more across time and react sooner to other symptom changes and treatment. These studies have taken place over a time span from a few months to up to 9 years (Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015; Karp et al, 2004; van Eeden, van Hemert, Carlier, Penninx, & Giltay, 2019). Bringmann et al (2015) found in their longitudinal network analysis of depression that during 14 weekly assessments, suicidal thoughts registered a high level of network outdegree (i.e., were likely to trigger other symptoms) and low indegree (i.e., not likely to be influenced by other symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have indicated that suicidality is one of the most stable depressive symptoms over time (meaning it has low variability), whereas the opposite holds for depressed mood and anhedonia, which vary more across time and react sooner to other symptom changes and treatment. These studies have taken place over a time span from a few months to up to 9 years (Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015; Karp et al, 2004; van Eeden, van Hemert, Carlier, Penninx, & Giltay, 2019). Bringmann et al (2015) found in their longitudinal network analysis of depression that during 14 weekly assessments, suicidal thoughts registered a high level of network outdegree (i.e., were likely to trigger other symptoms) and low indegree (i.e., not likely to be influenced by other symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…Research has examined the homotypic (i.e., a disorder predicting itself at a later time point) and heterotypic (i.e., a disorder prospectively predicting another disorder) continuity of diagnoses or latent psychopathology factors, which may identify potential causal relationships between disorders that may reflect mechanisms underlying comorbidity (e.g., Shankman et al, 2009; Shevlin, McElroy, & Murphy, 2017; Snyder, Young, & Hankin, 2017). However, growing evidence suggests that individual symptoms may have different courses (van Eeden, van Hemert, Carlier, Penninx, & Giltay, 2018) and distinct genetic and environmental etiologies (e.g., Keller, Neale, & Kendler, 2007; Myung et al, 2012). Extending this evidence supporting the differential validity of individual symptoms, the network theory of psychopathology suggests that psychopathology is the result of causal relationships between individual symptoms (Borsboom, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory markers and depression have been linked, but effect sizes were generally small with limited clinical relevance for the individual patient 1 . Because depression is a heterogeneous disorder with large between-person variation 27 and symptomatology 28 , 29 , low-grade inflammation may only be strongly linked to a subset of depressive symptoms 30 , 31 . Thus, inflammation may be involved in the pathogenesis of a subset of MDD patients.…”
Section: Introductionmentioning
confidence: 99%